Book Review of: Sociology in Brazil, A Brief Institutional and Intellectual History - Pereyra, Diego (Serendipities. Journal for the Sociology and History of the Social Sciences, 2022)
How to tell the history of sociology in a peripheral country? Moreover, how to do it in a country as vast and complex as Brazil? This is a very difficult challenge to perform. Cordeiro and Neri´s book, Sociology in Brazil, published by Palgrave- Pivot in Sociology Transformed Series, was able to pull it off, though. The book aims to make an integrative reconstruction of sociology in Brazil during a time that dates back to almost 130 years ago. The volume deserves to be read since it gives a brief but prolific analytical description of intellectual and institutional development of the discipline in that country. In addition, this historical account offers a reinterpretation of home traditional narratives from a perspective that combines cognitive and institutional factors. So, it aims to achieve a comprehensive narration of the dispute among local sociological traditions, institutions from different cities and regions and also local key intellectual figures.